Stitch! the movie - Disney (Maitland, FL Advance Publishers, L.C. Burbank, Calif. : Distributed by Buena Vista Home Entertainment, 2006)
Stitch was experiment 626, now the 625 other alien experiments are landing on Earth and it's up to Lilo and Stitch to rescue these outrageous 'cousins' before they're captured by the evil Captain Gantu.